(untitled) (World Science, 2020)
The paper considers one of the tasks that need to be solved when developing complex monitoring systems of metal’s status, which is to ensure the stability of the supply voltage, and the results of compensatory voltage stabilizer development are given. The analysis results of the adopted circuit solutions correctness are shown and the conformity of the stabilized power supply parameters to the given conditions is proved.